Physical Activity and Low Back Pain in Medical Student - Filza Febiningrum; Dhoni Akbar Ghozali; Siti Munawaroh; Yunia Hastami (Universitas Ahmad Dahlan, 2021)
Low back pain (LBP) is a disease that can negatively affect all people with the prevalence of 38% per year. Risk factors of LBP are lifestyle and physical activities, incorrect sitting and lifting position, age, and psychological factors such as stress. Medical students become one of the risk groups of LBP due to limited time of physical activity that leads to inactivity. This research is aiming to understand the correlation between physical activity and LBP in medical students. This is an analytical observational research with cross sectional study design. The subject was 100 medical students of Sebelas Maret University who fulfill the criteria of sampling. Sampling was done using purposive sampling technique. Data was collected using IPAQ-SF (International Physical Activity Questionnaire Short Form) and Oswestry Low Back Pain Disability Index questionnaire. Data was then analyzed with Rank Spearman Correlation Test. As a result of this research, 57 medical students of Sebelas Maret University do moderate physical activity and 91 medical students have LBP with minimal disability. Results showed there was no significant correlation between physical activity and LBP with p = 0,064 (p>0,05) and there was also no significant correlation between gender and LBP with p = 0,176 (p>0,05) in medical students of Sebelas Maret University.In conclusion, there was no significant correlation between physical activity, gender, and LBP in medical students of Sebelas Maret University.